Induction of 2D grid structure from amphiphilic pyrene assembly by charge transfer interaction. (March 2021) - Shen, Bowen; Park, Il-Soo; Kim, Yongju; Wang, Huaxin; Lee, Myongsoo
Abstract: In this work, we report the spontaneous formation of 2-dimensional (2D) grid structures through charge transfer interactions of pyrene amphiphiles. Pure pyrene amphiphiles self-assemble into long nanofibers in aqueous solution. Remarkably, these aqueous nanofibers transform into a 2D grid structure upon charge transfer complexation. The charge transfer interaction induces crystallization of the aromatic core part, leading to discrete micelles with up and down hydrophilic chains, and hydrophobic side faces. Eventually, the anisotropic micelles grow in a 2-dimensional way through side-by-side interactions to form unusual 2D grid structures. Graphical abstract: Image, graphical abstract